Removal torque evaluation of three different abutment screws for single implant restorations after mechanical cyclic loading - Paepoemsin T. (2017)
© 2016 CIC Edizioni Internazionali Unauthorized reproduction of this article is prohibited. Purpose. The aim of this study was to evaluate the removal torque of three different abutment screws and pull out strength of implant-abutment connection for single implant restorations after mechanical cyclic loading. Methods. The study was performed in accordance with ISO 14801:2007. Three implant groups (n=15) were used: group A, PW Plus® with flat head screw; group B, PW Plus® with tapered screw; and group C, Conelog® with flat head screw. All groups had the same implant-abutment connection feature: cone with mandatory index. All screws were tightened with manufacturer’s recommended torque. Ten specimens in each group underwent cyclic loading (1x106 cycles, 10 Hz, and 250 N). Then, all specimens were un-tightened, measured for the removal torque, and underwent a tensile test. The force that dislodged abutment from implant fixture was recorded. The data were analysed using independent sample t-test, ANOVA and Tukey HSD test. Results. Before cyclic loading, removal torque in groups A, B and C were significantly different (B > A > C, P < .05). After cyclic loading, removal torque in all groups decreased significantly (P < .05). Group C revealed significantly less removal torque than groups A and B (P < .005). Tensile force in all groups significantly increased after cyclic loading (P < .05), group A had significantly less tensile force than groups B and C (P < .005). Conclusions. Removal torque reduced significantly after cyclic loading. Before cyclic loading, tapered screws maintained more preload than did flat head screws. After cyclic loading, tapered and flat head screws maintained even amounts of preload. The tensile force that dislodged abutment from implant fixture increased immensely after cyclic loading.